Etude et simulation des Réseau de Bragg sur fibre optique pour la compensation de la dispersion chromatique dans les systèmes de transmission optique haut débit. - Reggab Fatima (University of Amar Telidji – Laghouat Faculty of Technology Department of Electrical Engineering, 2023)
Fiber optics are now one of the most widely used means of high-speed optical communication in long-distance transmission. Like others, fiber optics have certain factors limiting propagation such as chromatic dispersion and losses. The purpose of our work is to compensate for the effect of chromatic dispersion in =1.55μm wavelength "" λ in WDM multiplexing systems using Bragg Network Fiber Technology (FBG) according to the simulation software. OPTISYSTME By comparing the results obtained through the use of the two technologies, the use of Bragg network fibers is the best option to compensate for the dispersion effect caused by single-mode fibers .
Spécialité :Réseaux et Télécommunications